Ground crickets singing in volcanic warm "islets" in snowy winter: Their seasonal life cycles, photoperiodic responses and origin. Issue 4 (13th July 2016) - Masaki, Sinzo; Soma, Masayuki; Ubukata, Hidenori; Katakura, Haruo; Ichihashi, Rie; He, Zhuqing; Ichijô, Nobuaki; Kobayashi, Norio; Takeda, Makio
Abstract: The ground cricket Dianemobius nigrofasciatus overwinters as an egg in Japan, being univoltine in Hokkaido and northern Honshu and bivoltine farther south. In Hokkaido, however, this cricket is heard singing in winter in several fumarolic fields covered with moss and grasses locally known as " bokke ". In such warm "islets" the adult density was high in early summer and again in autumn, indicating that the cricket is bivoltine in contrast to the univoltine life cycle outside the bokke habitats in Hokkaido. Eggs laid by females collected at regular intervals from a bokke habitat showed a clear seasonal cycle of diapause incidence. At 26°C, the bokke strains produced non‐diapause eggs under long days and diapause eggs under short days as in the southern bivoltine populations, although the critical day‐length was longer than in the south. Several strains derived from non‐ bokke habitats in Hokkaido and northern Honshu produced high percentages of diapause eggs under long days as well as short days as expected for the univoltine life cycle. Winter adults singing in bokke habitats could be either survivors of the autumn generation or individuals derived from eggs laid in autumn and then matured in response to the high soil temperature. In the laboratory, the proportion of egg diapause in short days was decreased by selection only for several generations. Phylogenetic trees of bokke and non‐ bokke populations, based on both the nucleotide sequence of the mitochondrial COI gene and four allozyme loci, suggest that bokke populations have not been isolated from non‐ bokke populations for an evolutionarily significant time. Abstract : In " bokke " habitats, grounds with geothermal spots free from snow cover, the ground cricket, Dianemobius nigrofasciatus, is bivoltine in contrast to univoltine cycle in the non‐bokke habitats of Hokkaido, showing genetic differentiation in the egg‐diapause response to photoperiod. Analyses of allozyme loci and COI gene arrangements suggests no general genetic divergence between bokke and non‐ bokke populations, probably because of the high migratory activity of the long‐winged form.